Uses and perfomance of the IUCN susytem of management categories for protected areas. Speaking a common language / Bishop Kevin, Nigel Dudley, Adrián Phillips - Bishop, Kevin (2004)
The apeaking a common language Project, the emergence of an international system of protected area management categories; evaluating the original purposes of the IUCN categories, encouraging national proted area systems; evaluating the new uses made of the IUCN categories, providing a basis for legislation; using the IUCN categories more effectively the definition and purposes the categories dissemination of information; conclusions and recommendations